Why David sometimes wins leadership, organization, and strategy in the California farm worker movement - Ganz, Marshall, 1943- (Oxford : Oxford University Press, 2009)
In this work, Marshall Ganz tells the story of the United Farm Worker's ground-breaking victory in 1966, drawing out larger lessons from this dramatic tale. A longtime leader in the movement and current lecturer in public policy at Harvard, he offers unique insight.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United Farm Workers -- History; Agricultural laborers -- Labor unions -- California -- History; Migrant agricultural laborers -- Labor unions -- California -- History; Agricultural laborers -- California -- History